DISCOURSE ON PROFIT SHARING FUND POLICY BETWEEN CENTRAL GOVERNMENT AND REGIONAL GOVERNMENT IN OIL AND GAS MINING SECTOR IN INDONESIA - Lubis, Khairil Afandi; Akbar Nasution, Faisal; Afnila, Afnila; NAM Sihombing, Eka (NOMOI Law Review, 2024)
Revenue Sharing Fund (DBH) in the oil and gas sector is one of the important instruments in regulating the distribution of revenue between the central government and producing regions in Indonesia. This DBH policy is designed to ensure fair revenue sharing between the center and regions. However, its implementation often encounters various problems, such as delays in distribution, unfairness in distribution, and the impact of fluctuations in world oil and gas prices. The type of research used is normative legal research with a prescriptive juridical approach to understand the discourse on oil and gas DBH policies in Indonesia. The results of the study show that there is a discourse on the Revenue Sharing Fund policy in the oil and gas sector in Indonesia showing that this policy still faces a number of serious challenges, such as delays in distribution, unfairness in distribution, lack of transparency, and the impact of fluctuations in global oil and gas prices. To improve this policy, reforms are needed in the distribution mechanism, revision of the distribution formula, increased transparency, and economic diversification in producing regions